Darurat Moderasi Beragama Di Tengah Pandemi Corona Virus Desease 2019 (Covid-19) - Abdul Syatar Abdul Syatar; Muhammad Majdy Amiruddin; Arif Rahman; Islamul Haq (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2020)
Abstract The purpose of this article is to elaborate on the essence of maintaining religious moderation amid the covid pandemic 19. The social-religious approach was conducted by observing the facts that occur in society. The result indicates that moderate priorities in religion during the covid pandemic 19 became a necessity. Consequently, maintaining personal safety and the wider community should become a priority due to the absence of alternative rather than forcing the will to carry out worship in the mosque or in certain places. Islamic law provides rukhsah when the ummah is not in proper conditions to do such rituals like praying in the mosque. On the other hand, people are required to better understand fiqh in the pandemic of Covid 19 by not leaving conventional fiqh. Adapting the religious moderation during or after the covid pandemic 19 becomes a necessity, especially relations between humans by avoiding and blocking the transmission of the virus in various ways. Acceptance of the new habit caused by covid 19 from various aspects, especially the worship habits of the people should be considered. The principle of avoiding harm is more important than carrying out benefits is one of the ways in Islam to maintain religious moderation. Keywords: Religious Moderation; Pandemic; Corona Virus; Covid 19